Fish to 2030: Prospects for fisheries and aquaculture - World Bank; Msangi, Siwa; Kobayashi, Mimako; Batka, Miroslav; Vannuccini, Stefania; Dey, Madan M.; Anderson, James L.; Kelleher, Keiran; Singh, Kehar; Brummet, Randall (World Bank, 2013)
This study employs IFPRI’s IMPACT model to generate projections of global fi sh supply and demand. IMPACT covers the world in 115 model regions for a range of agricultural commodities, to which fi sh and fi sh products are added for this study. As is the case with most global modeling work, an important value that IMPACT brings to this study is an internally consistent framework for analyzing and organizing the underlying data. However, there are known data and methodology issues that arise from choices made by the key researchers for the purposes of maintaining computational tractability, internal analytical consistency, and overall simplicity.